The Role and Impact of Artificial Intelligence on Supply Chain Management: Efficiency, Challenges, and Strategic Implementation - Ismaeil, Mohamed kamal Aldin (Journal of Ecohumanism, 2024)
This research paper delves into the transformative impact of artificial intelligence (AI) on supply chain management, focusing on enhancing demand forecasting, operational efficiency, and customer satisfaction, while also managing costs and streamlining logistics operations. The adoption of AI in supply chains offers significant opportunities to improve service delivery and operational capabilities, which are crucial for maintaining competitiveness in the rapidly evolving business landscape. The study underscores the importance of AI technologies in reshaping supply chain dynamics by providing a comprehensive analysis of both the benefits and challenges associated with its implementation. Key benefits highlighted include the optimization of inventory management, enhanced accuracy of demand forecasting, reduced operational costs, and improved customer service. These enhancements are pivotal in achieving a competitive edge and adapting to changing market demands.However, the integration of AI into supply chains is not devoid of challenges. The paper identifies critical obstacles such as the need for significant cultural shifts within organizations, data security concerns, and the complexities of navigating legal and regulatory frameworks. These challenges require strategic management to ensure successful AI adoption and to mitigate associated risks.The research includes case studies of Arab companies that have integrated AI into their supply chains, offering practical insights into the real-world application of these technologies. These examples demonstrate both the potential rewards and the difficulties encountered, providing a balanced perspective on the practicalities of AI deployment in supply chain settings.In conclusion, while AI presents substantial opportunities for advancing supply chain management, it also necessitates careful consideration of various implementation challenges. The paper provides strategic recommendations for Arab companies aiming to leverage AI technologies effectively. These guidelines emphasize the need for thorough planning, continuous risk assessment, and fostering an adaptive organizational culture. By addressing these key areas, companies can harness the full potential of AI to enhance their supply chain operations and achieve sustainable growth.